(untitled) (TERRA LATINOAMERICANA, 2025)
Arbuscular mycorrhizal fungi (AMF) promote the development of wild and cultivated plants and are, therefore, critical in agroforestry systems. In our study, we evaluated the ef fectiveness of three inocula of arbuscular mycorrhizal fungi of AMF from three dif ferent land uses: vegetation islands and open areas of agroforestry system “milpa-chichipera”, and xeric scrub on the growth and nutrition of lettuce plants (Lactuca sativa L.) at semiarid Tehuacan-Cuicatlan Valley, Puebla-Oaxaca, Mexico. A sterilized substrate was prepared based on a 50/50 (v/v) mixture of soil and silica sand. Three inoculation treatments were established with 50 g of soil inoculum which included AMF from the three land uses and a control without inoculation, with five replicates. The plants were grown for three months, and at the end of the experimental period, the aerial part was harvested to evaluate fresh and dry weight, leaf area and contents of water, leaf chlorophyll, N and P in plant. All inocula favored the growth and nutrition of lettuce compared to the control. However, inoculated plants with AMF from vegetation islands and open areas of the agroforestry system had a better response than those inoculated with AMF from xeric scrub. Likewise, the three inocula increased the chlorophyll of the leaves in the plants; however, these were higher in inoculated plants with AMF from the vegetation islands of the agroforestry system and xeric scrub. Additionally, tissue P and N contents were higher in inoculated plants with AMF from agroforestry system. The inocula from agroforestry system were more ef fective for lettuce crop than the inoculum from xeric scrub; however, all three inocula could be potential mycorrhizal biofertilizers in this semiarid ecosystem.